378 تنمية رأس المال البشري وثلاثية التعليم والصحة والسكان في ضوء تطبيقات الذكاء الاصطناعي : Human Capital Development and The Triad of The Education, Health, and The Population In Light of Artificial Intelligence Applications - مجدة إمام دسوقي عبد الجليل، زينات طبالة وأخرون (معهد التخطيط القومي, 2026)
يتناول البحث أثر النمو السكاني والتباين الديموغرافي على تحديات التنمية المستدامة. ويؤكد على أن تنمية رأس المال البشري هي المدخل الأساسي لتحقيق تنمية شاملة لا تستثني أحدًا. ويركز على محاور التعليم والصحة والعمل كركائز رئيسية لتعزيز الحماية الاجتماعية وبناء القدرات. كما يبرز دور الذكاء الاصطناعي في دعم التعليم والتدريب والرعاية الصحية وتحسين جودة الحياة. ويؤكد على أهمية الاستخدام المسؤول للتكنولوجيا في تمكين الأفراد ودمجهم في سوق العمل المستقبلي. The study addresses rapid population growth and demographic disparities as key challenges to sustainable development. It emphasizes human capital development as the main pathway to inclusive development based on the “leave no one behind” principle. Education, health, and employment are identified as core pillars for strengthening social protection and building human capabilities. AI technologies are highlighted as tools that enhance healthcare, education, and career development while improving quality of life. The study also stresses ethical and responsible use of AI to support inclusion, equal opportunities, and future workforce integration.